The Personalization of Politics in Media Context: Discourse Analysis of Political Talk-Show - Melikidze, Giorgi (Politics / პოლიტიკა; 2018: მესამე ნომერი, 2018)
Whitin the last decades political communication has suffered transformation in the world’s ongoing globalization conditions. Political personalization is the main characteristic of political communication not only in transitional democracies, but in developed democracies too. There are three types of political personalization in academic literature: Media personalization, institutional personalization and electoral personalization. The present article aims to examine political personalization in media context in Georgia. In accordance with the research hypothesis weak institutionalization of party system promotes media personalization. It should be determined by the results of study, whether there is media personalization? What characteristics is detected? How it is connected to the party system institutionalization? The Survey results suggest, big part of time in media coverage is devoted to the problem consideration. Nevertheless, there is political personalization in Georgia and it has negative character.              In the research are used qualitative methods: The Analysis of personal coverage (Issue / Process); Distribution of the  personalization evidence by types; The resaerch of the character and quality of personalization. In-depth interviews with representatives of political parties and selected electorate.
Keywords: Political Personalization, Media, Negative Context, Talk-Show